Chemical signalling behaviour in intrasexual communication of lizards lacking femoral pores. (12th March 2020) - Bruinjé, Andre C.; Coelho, Felipe E. A.; Maggi, Bruno S.; Costa, Gabriel C.
Abstract: Signals that are used in animal communication may have multiple sensorial channels and functions. Animal communication integrates very distinct mechanisms such as behaviour, morphology and physiological secretions. Chemical signals occur in several contexts and are known to have a role in sexual selection. In many lizards, pheromones secreted through femoral pores are used to attract females and demark territory dominance. In lizard species without femoral pores, however, study of chemical signalling is negligible. Lizards of the genus Tropidurus have no ventral pores, but express melanic patches in their ventral thighs and cloacae (body regions linked to chemical communication in other lizards), which may play a role in both visual signalling and chemical signalling. Here, we describe the occurrence of pelvic rubbing—a chemical signalling behaviour—in two Tropidurus species, displayed in intraspecific agonistic intrasexual staged encounters. In addition, we compile a list of currently reported species that display this behaviour, checking for its social contexts and presence/absence of secretion pores. We analysed behaviours in conspecific trials between males of Tropidurus semitaeniatus and of T. hispidus during their breeding season. In T. semitaeniatus, displays of pelvic rubbing elicited aggressive responses from the opponents. Tropidurus hispidus, however, did not react to these conspecific displays. Pelvic rubbings were also partially linked to defecation in both species, which is likely due to secretions from internal urodeal glands expelled during defecation. Also, high rates of tongue flick behaviours during the encounters support the hypothesis that these lizards make use of chemical communication. Our observations corroborate previous suggestions that glandular scales— scales covered by generation glands produced at the epidermis across the lizards' shedding cycles— are present in their melanic ventral patches. Our work also highlights the potential of characterizing such ventral patches as multimodal signalling badges. Further, we investigated the contexts in which pelvic rubbing is displayed adding to our understanding of the role played by chemical signalling in lizards without femoral pores.